2021
DOI: 10.1038/s41541-021-00326-3
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-induced, but not natural immunity, against the Streptococcal inhibitor of complement protects against invasive disease

Abstract: Highly pathogenic emm1 Streptococcus pyogenes strains secrete the multidomain Streptococcal inhibitor of complement (SIC) that binds and inactivates components of the innate immune response. We aimed to determine if naturally occurring or vaccine-induced antibodies to SIC are protective against invasive S. pyogenes infection. Immunisation with full-length SIC protected mice against systemic bacterial dissemination following intranasal or intramuscular infection with emm1 S. pyogenes. Vaccine-induced rabbit ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(38 reference statements)
2
7
0
Order By: Relevance
“…A study by Kachroo et al [ 59 ] revealed a positive correlation between sic and genes involved in the host immune response and inflammation when they examined the dual RNA-seq transcriptomes of S. pyogenes and host skeletal muscle from infected non-human primates. In addition, vaccination-induced anti-sic antibodies were effective in bacterial clearance in rabbit, mice, and in an ex vivo whole body assay [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kachroo et al [ 59 ] revealed a positive correlation between sic and genes involved in the host immune response and inflammation when they examined the dual RNA-seq transcriptomes of S. pyogenes and host skeletal muscle from infected non-human primates. In addition, vaccination-induced anti-sic antibodies were effective in bacterial clearance in rabbit, mice, and in an ex vivo whole body assay [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This forms the basis of the classic “Lancefield” assay 18 , which measures the opsonophagocytic capacity of donor plasma antibodies as a marker of resistance to invasive infection. Subcutaneous 19 – 21 , intramuscular 22 , 23 and intranasal 24 , 25 vaccination with adjuvanted protein vaccines appear effective at preventing even lethal invasive infections in mouse models of infection. Furthermore, passive transfer of immunity using antisera and pooled human intravenous immunoglobulin (IVIg) have all successfully induced immunity in animal models, particularly when highly concentrated 13 .…”
Section: Immunity To Invasive Infectionmentioning
confidence: 99%
“…In a longitudinal cohort of Fijian children, there was no association between the time to next Strep A skin infection and total serum IgG antibody titres to the M protein semi-conserved C-repeat region J8 peptide following primary skin infection 52 . It is important to note that vaccine-induced and natural immunity may differ significantly 23 .…”
Section: Anti-strep a Antibodiesmentioning
confidence: 99%
“…In conclusion, it is clear that natural IMI itself does not elicit complete protection against reinfection, so that any vaccine would have to improve on the natural immune response. An example is provided by the antibody response to Streptococcus pyogenes inhibitor of complement SIC: natural infection does not elicit neutralizing antibodies, whereas vaccination with the recombinant protein does [44]. Accordingly, the new vaccines would protect against infectious diseases by eliciting "unnatural immunity"; that is, immune responses that are of a different nature and directed to different antigens from those elicited by natural infections [5].…”
Section: The Issue Of Protection Induced By Mg Infectionsmentioning
confidence: 99%